2020
DOI: 10.1080/15592294.2020.1803467
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide microRNA expression analysis in human placenta reveals sex-specific patterns: an ENVIRONAGE birth cohort study

Abstract: There is an increasing interest in microRNAs (miRNAs) as they are of utmost importance in gene regulation at the posttranscriptional level. Sex-related susceptibility for non-communicable diseases later in life could originate in early life. Until now, no data on sex-specific miRNA expression are available for the placenta. Therefore, we investigated the difference by sex of newborn's miRNA expression in human placental tissue. Within the ENVIRONAGE birth cohort, miRNA and mRNA expression profiling was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
2
11
0
Order By: Relevance
“…Previous studies analyzing miRNA expression in first and/or third trimester placentae have used microarray technology and most examined very few samples (N=2-6 in each group). 25,47,48,90 There are currently few NGS miRNA profiles of the placenta, and our study is the first to profile both first and third trimester placentae with NGS and a large sample size. We successfully validated all six selected miRNAs using qRT-PCR and an independent cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies analyzing miRNA expression in first and/or third trimester placentae have used microarray technology and most examined very few samples (N=2-6 in each group). 25,47,48,90 There are currently few NGS miRNA profiles of the placenta, and our study is the first to profile both first and third trimester placentae with NGS and a large sample size. We successfully validated all six selected miRNAs using qRT-PCR and an independent cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the use of high-throughput sequencing, as opposed to other techniques such as arrays, allows for greater confidence regarding differential expression, since all known miRNA species previously annotated in the human genome are considered. Although other studies have identified sexually dimorphic miRNA expression in the placenta, these studies were small, [72] and most of them were in placenta disease states where differences may be attributed to development of placental dysfunction which may be the result of sexually dimorphic miRNA regulation of these sexually dimorphic disease states [71, 73].…”
Section: Discussionmentioning
confidence: 99%
“…To assist the translation of the identified CpGs into biological pathways, the DNA methylation level of the CpGs were correlated to the gene expression data available in the ENVIRONAGE birth cohort. Global gene expression profiling by microarrays was performed in cord blood samples using a method described previously [68]. 44 samples which were available in both DNA methylation and global gene expression profiles were used in searching for RNA probes that are correlated with the selected CpGs.…”
Section: Functional Annotation Of the Selected Cpgsmentioning
confidence: 99%